2017
DOI: 10.5194/acp-17-9853-2017
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase composition changes and reactive oxygen species formation during limonene oxidation in the new Cambridge Atmospheric Simulation Chamber (CASC)

Abstract: Abstract. The chemical composition of organic aerosols influences their impacts on human health and the climate system. Aerosol formation from gas-to-particle conversion and in-particle reaction was studied for the oxidation of limonene in a new facility, the Cambridge Atmospheric Simulation Chamber (CASC). Health-relevant oxidising organic species produced during secondary organic aerosol (SOA) formation were quantified in real time using an Online Particlebound Reactive Oxygen Species Instrument (OPROSI). Tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 78 publications
(111 reference statements)
7
36
0
Order By: Relevance
“…PM-bound ROS, as illustrated in Figure 2, are formed non-enzymatically on particles during the particle formation processes or from the catalytic reactions of inhaled PM components (e.g., quinones and transition metals) in the presence of O 2 , which has been described in Section 2.3. The photooxidation of hydrocarbon precursors by atmospheric oxidants (e.g., •OH, O 3 and •NO 3 ) can generate a large amount of ROS including ROOH and free radicals (e.g., RO•, R•, ROO• and HO 2 •), as shown in reactions (9)-(13) [120]. These reactive species (with lifetimes ranging from minutes to days in the atmosphere) are key intermediates leading to formation of SOA [120].…”
Section: Pm-associated Ros: Pm-bound Ros and Pm-induced Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…PM-bound ROS, as illustrated in Figure 2, are formed non-enzymatically on particles during the particle formation processes or from the catalytic reactions of inhaled PM components (e.g., quinones and transition metals) in the presence of O 2 , which has been described in Section 2.3. The photooxidation of hydrocarbon precursors by atmospheric oxidants (e.g., •OH, O 3 and •NO 3 ) can generate a large amount of ROS including ROOH and free radicals (e.g., RO•, R•, ROO• and HO 2 •), as shown in reactions (9)-(13) [120]. These reactive species (with lifetimes ranging from minutes to days in the atmosphere) are key intermediates leading to formation of SOA [120].…”
Section: Pm-associated Ros: Pm-bound Ros and Pm-induced Rosmentioning
confidence: 99%
“…The photooxidation of hydrocarbon precursors by atmospheric oxidants (e.g., •OH, O 3 and •NO 3 ) can generate a large amount of ROS including ROOH and free radicals (e.g., RO•, R•, ROO• and HO 2 •), as shown in reactions (9)-(13) [120]. These reactive species (with lifetimes ranging from minutes to days in the atmosphere) are key intermediates leading to formation of SOA [120]. As shown in Table 2, PM-bound ROS such as radicals and ROOH have been characterized in prior research directly by 9,10-bis (phenylethynyl) anthracene-nitroxide (BPEAnit), EPR/ESR techniques, and 4-nitrophenyl boronic acid (NPBA) assay.…”
Section: Pm-associated Ros: Pm-bound Ros and Pm-induced Rosmentioning
confidence: 99%
“…The current work will focus on the relative toxicities of different SOA systems, as field studies have repeatedly shown that SOA often dominate over primary aerosols (e.g., PM emitted directly from combustion engines) even in urban environments (Zhang et al, 2007;Jimenez et al, 2009;Ng et al, 2010). Furthermore, in recent years, there have been an increasing number of studies on the health effects of SOA formed from the oxidation of emitted hydrocarbons, demonstrating their potential contribution to PM-induced health effects (McWhinney et al, 2013;Rattanavaraha et al, 2011;Kramer et al, 2016;Lund et al, 2013;McDonald et al, 2010;McDonald et al, 2012;Baltensperger et al, 2008;Arashiro et al, 2016;Platt et al, 2014;Gallimore et al, 2017). However, the cellular exposure studies involving SOA focused on SOA formed from a single precursor and included different measures of response (e.g., ROS/RNS, inflammatory biomarkers, gene expression; Arashiro et al, 2016;Lund et al, 2013;McDonald et al, 2010McDonald et al, , 2012Baltensperger et al, 2008;Lin et al, 2017).…”
Section: W Y Tuet Et Al: Inflammatory Responses To Soa Generated Fmentioning
confidence: 99%
“…CC BY 4.0 License. (c) PB-ROS contents in primary (ROS POA ) and secondary organic aerosol (ROS SOA ) from wood and coal burning), in SOA from α-pinene (this study, as well as literature data for 2stroke scooters (2s_Scooter) (Platt et al, 2014), and for SOA from limonene (Gallimore et al, 2017) and oleic acid (Fuller et al, 2014).…”
Section: Atmospheric Implicationsmentioning
confidence: 79%
“…Our values for ROS PM2.5 (0.07 ± 0.04, and 0.09 ± 0.06, for Beijing_Haze, and Beijing_Reference, respectively) are in line with other online measurements reported by Huang et al (2016) for Beijing (0.12 ± 0.05 and 0.10 ± 0.05 nmol µg -1 in winter 2014 and spring 2015, respectively), and the value of ROS PM1 (0.13 ± 0.06 nmol µg -1 ) for Bern is not significantly different from the values in China. Figure 5b indicates the PB-ROS contents attributed to different sources identified in Bern and Beijing, and Figure 5c summarizes the PB-ROS contents from our own laboratory measurements of different emission sources (see Section 2.1), complemented by literature values, i.e., 2-stroke scooter emissions (2s_scooter (Platt et al, 2014)), as well as SOA from limonene and oleic acid oxidation (Gallimore et al, 2017;Fuller et al, 2014). The PB-ROS contents in primary emissions (ROS POA ) from 2-stroke scooters or wood and coal burning are about 4 to 25 times lower than those in the corresponding SOA samples (ROS SOA , see Section 2.4).…”
Section: Source Contributions To Pb-rosmentioning
confidence: 99%